Hematological and blood chemistry parameters of a Podocnemis vogli and P. unifilis captive population in Colombia - Rodríguez-Almonacid, Cristian; Fuentes-Rodríguez, Gustavo; González, Leidy P.; Moreno-Torres, Carlos; Matta, Nubia E. (Frontiers in Veterinary Science, 2022)
Podocnemididae family is seriously affected by anthropogenic factors, that is why almost all members of these family are threatened according to the IUCN red list. The biology and ecology of these species is poorly known, as well as the haematological and serum chemistry reference intervals that allow clinical action and decision-making conservation programs. Based on this, the objective of this study is to establish the haematological and blood chemistry parameters of the Savannah side-necked turtle (Podocnemis vogli) and Yellow-spotted river turtle (P. unifilis) maintained in captivity at the Estación de Biología Tropical Roberto Franco (Villavicencio-Colombia). Forty-nine captive turtles of the species P. vogli (n=28) and P. unifilis (n=21) were sampled to determine haematological and serum chemistry parameters. Blood was collected from jugular vein of males and females’ turtles of both species. T-student and Mann-Whitney-Wilcoxon tests were used to compare values between the parameters evaluated against genders and sizes. Reference intervals were calculated for haematological and biochemistry values of each species. Some assessed parameters showed significant differences between males and females of both species. Most of the analyzed parameters showed similar reference intervals in both species. In this study we report values and propose haematological and serum chemistry reference intervals for P. vogli and P. unifilis, which can be used in the clinical diagnosis of these reptiles and in future research.